Avaliação do potencial de reciclagem e ciclo de vida de blendas contendo polietileno e amido termoplástico - Ruthe Rebello Pires Novaes (2015)
Based on the series of ISO 14000 norms, this work employed the Life Cycle Assessment methodology (LCA) associated with Matrix Approaches to Abridged Life Cycle Assessment, to compare the life cycle of blown thin films of LDPE and LDPE and thermoplastic starch (TPS). Moreover, the recyclability of the LDPE and LDPE/starch blends were also investigated by submitting the materials to multiple extrusion cycles. Both the polymer and the polymer blend were studied in two ways: the first approach involved the premanufacturing, manufacturing, packaging and grounding, and the second approach also included the recycling phase. In both, the choice of material, energy consumption, solid, liquid and gaseous waste was evaluated. To proof the feasibility of the use and recyclability of the materials, samples of LDPE and LDPE/TPS were submitted to 1, 5 and 10 cycles of extrusions to simulate recycling steps, samples were characterized by mechanical tensile tests, electron microscopy, differential scanning calorimetry, capillary rheometer, dynamic mechanical analysis and contact angle. The results obtained from the LCA showed a superior environmental performance of blends of 12% when recycled and grounded in comparison to LDPE. The blends also exhibited a high degree of recyclability (that is, the absence of significant changes in properties over the reprocessing cycles) and comparable to that of pure LDPE. These combined results indicate the usefulness of promoting recycling steps involving blends containing natural polymers in order to generate less severe environmental impacts